2001
DOI: 10.1097/00007632-200112010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Efficacy, and Cost Effectiveness of Evidence-Based Guidelines for the Management of Acute Low Back Pain in Primary Care

Abstract: The immediate results from evidence-based care are marginally better than those from good usual care, but in the long term, evidence-based care achieves clinically and statistically significant gains, with fewer patients requiring continuing care and remaining in pain. Consumers approve of evidence-based care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 23 publications
2
98
0
4
Order By: Relevance
“…Improvement of low back and neck pain in this feasibility study showed to be comparable to findings in other studies [12,30,33,34].…”
Section: Main Clinical Findingssupporting
confidence: 90%
“…Improvement of low back and neck pain in this feasibility study showed to be comparable to findings in other studies [12,30,33,34].…”
Section: Main Clinical Findingssupporting
confidence: 90%
“…For example, Vos et al [11] found that while 97% of patients with a new episode of neck pain received advice, 18% were advised to rest. In Australia, referrals for imaging as identified in this and other studies [2,27] were much higher than those previously reported for patients with new neck pain (9% [11]) and new LBP (2-18% [24,26]). These findings suggest an overutilization of imaging by GPs in Australia, especially in light of the low prevalence (\1%) of serious spinal pathology (fracture, tumour) [28] and of the fact that routine imaging has been shown to not have a beneficial influence on clinical outcomes [29].…”
Section: Discussionmentioning
confidence: 52%
“…Seventeen studies used a minimum level of pain or 'symptoms' as a proxy for recovery; however, no two studies did so in exactly the same way (Table 1). Three recovery measures required the complete absence of pain, whereas three others fixed a cut-off score on the instrument [39,40,60,66] that categorised subjects with minimal pain levels as recovered. The remaining studies gave a description of the symptomatic state necessary to indicate recovery.…”
Section: Data Extractionmentioning
confidence: 99%